2004
DOI: 10.1038/sj.ejhg.5201204
|View full text |Cite
|
Sign up to set email alerts
|

Association between a polymorphism in the carboxyl ester lipase gene and serum cholesterol profile

Abstract: Carboxyl ester lipase (CEL) is involved in the hydrolysis and absorption of dietary lipids, but it is largely unknown to what extent CEL could be involved in determining the serum lipid levels. The C-terminal part of CEL consists of a unique structure with proline-rich O-glycosylated repeats of 11 amino-acid residues each. The common variant of the human CEL gene contains 16 proline-rich repeats, but there is a high degree of polymorphism in the repeated region. While the biological function of the polymorphic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…Thus, these results indicate a possible association of CEL VNTR lengths with the disease pathogenesis of ALC, however, the definite repeat lengths cannot be defined in this stage. A possible pathophysiological explanation for how CEL VNTR length contributes to ALC development might be the determination of plasma lipid levels, as CEL VNTR length seems to influence total and low density lipoprotein cholesterol levels [32]. This would be in line with findings in a recent genome wide associations study that identified three risk loci for ALC involved in lipid metabolic processes [33].…”
Section: Discussionsupporting
confidence: 58%
“…Thus, these results indicate a possible association of CEL VNTR lengths with the disease pathogenesis of ALC, however, the definite repeat lengths cannot be defined in this stage. A possible pathophysiological explanation for how CEL VNTR length contributes to ALC development might be the determination of plasma lipid levels, as CEL VNTR length seems to influence total and low density lipoprotein cholesterol levels [32]. This would be in line with findings in a recent genome wide associations study that identified three risk loci for ALC involved in lipid metabolic processes [33].…”
Section: Discussionsupporting
confidence: 58%
“…CEL is also made and secreted by hepatocytes and, in humans, by macrophage and endothelial cells (32), but its roles in plasma and hepatic cholesterol metabolism remain unclear. Two independent studies showed a direct correlation between plasma CEL and LDL cholesterol levels in humans (33,34). On the other hand, studies with human HepG2 cells, as well as hepatocytes from control and Cel Ϫ/Ϫ mice, demonstrated a role for CEL in intracellular hydrolysis of HDL-CE (20,35).…”
Section: Discussionmentioning
confidence: 99%
“…However, the VNTR may be necessary for proper folding, secretion and stability (Bruneau et al 1997). An association between the total number of repeats and serum cholesterol profile has been reported (Bengtsson-Ellmark et al 2004). In addition, preliminary results indicate that exocrine dysfunction, often seen in diabetic patients, may be linked to common single-base insertions in the CEL VNTR (Raeder et al 2006).…”
Section: Introductionmentioning
confidence: 96%
“…The pancreatic CEL enzyme (E.C.3.1.1.13), also known as bile salt-stimulated or bile salt-dependent lipase, is secreted into the digestive tract where it is activated by the presence of bile salts, playing a role in cholesterol and lipid-soluble vitamin hydrolysis and absorption (Lombardo and Guy 1980). A fraction of the enzyme is also present in plasma and an interaction with plasma cholesterol and oxidized lipoproteins has been suggested (Bengtsson-Ellmark et al 2004;Caillol et al 1997). It is debated whether pancreatic CEL is transported from the duodenum to the blood (Bruneau et al 2003a, b), or if the plasma fraction is synthesized and secreted from macrophages and endothelial cells of the blood vessels, which have been shown to express low levels of CEL mRNA (Li and Hui 1998).…”
Section: Introductionmentioning
confidence: 99%